Deep Learning Approach in PAI Learning to Develop HOTS of Students of SMA Muhammadiyah PK Kottabarat Surakarta - Janati, Alya Amellia Ayu; Ali, Mohamad; Sholihah, Munaya Maratus (Universitas Muhammadiyah Surakarta, 2025)
This research is directed to examine in depth the application of the deep learning approach in the learning of Islamic Religious Education (PAI), examine its impact on the development of Higher-Order Thinking Skills (HOTS) of students, and uncover various challenges that arise along with their implementing solutions at SMA Muhammadiyah PK Kottabarat Surakarta. The research uses a qualitative method with a phenomenological approach to understand students' learning experiences and learning practices holistically in a real context. Data collection was carried out through participatory observation, in-depth interviews with teachers and students, and study of learning documents, which were then analyzed inducively with triangulation techniques to ensure the validity and credibility of the data. The findings of the study show that the application of the deep learning approach is able to increase active student involvement while developing HOTS, especially in the ability to analyze, evaluate, and create. PAI learning becomes more contextual, reflective, and student-oriented as a learning subject. In addition to improvements in the cognitive domain, this study also found positive changes in students' learning attitudes, such as increased activeness, critical power, and courage in expressing opinions. Thus, the deep learning approach not only has an impact on learning outcomes, but also forms a more independent and meaningful learning character. This research makes an empirical contribution to the development of deep learning-based PAI learning strategies and can be used as a practical reference for teachers in designing learning that is adaptive, innovative, and relevant to the demands of education in the modern era.